Roma Children Going to Primary School: The Contribution of Interagency Working to Support Inclusive Education - Joana Vale Guerra; Catarina Leitão (Karolinum Press, 2020)
Inclusive education can be promoted through partnerships between agencies supporting children and families, such as those in the scope of education, healthcare, social care, and welfare. Partnerships, often referred to as interagency working, were found to determine positive children's educational outcomes, and home-learning environment in previous studies. However, evidence on impact and best practices is still limited. The aim of this paper was to study facilitating factors, and impacts of interagency working for inclusive education. Perspectives of service providers were analysed in regard to a Portuguese project aiming to promote inclusive education and academic progress of children in primary school from a Roma community living in a low-income neighbourhood. Findings indicated that facilitating factors of interagency working for promoting inclusive education included political support, participation of service users in the planning and delivery of interventions, and informal and collaborative working relationships. Positive outcomes were found regarding improved children's school attendance and academic progress, and increased involvement of parents in children's education.